Internal Donors in Ziegler–Natta Systems: is Reduction by AlR3 a Requirement for Donor Clean‐Up?. Issue 5 (15th January 2018) - Zaccaria, Francesco; Vittoria, Antonio; Correa, Andrea; Ehm, Christian; Budzelaar, Peter H. M.; Busico, Vincenzo; Cipullo, Roberta
Abstract: Alkyl benzoates, phthalates, and succinates are used as "internal donors" (ID) to modify the surface of MgCl2 ‐supported Ziegler–Natta (ZN) catalysts for polypropylene production. Phthalates, in particular, are the working horses of this catalysis, but a REACH ban of these compounds for other applications has generated a desire from the market for phthalate‐free ZN catalysts, which has in turn triggered a search for alternatives and revamped research in the area. It has been reported that under polymerization conditions certain ID classes undergo an extensive exchange with alkoxysilane "external donors" (ED), which represents an important opportunity for surface fine‐tuning. ID clean‐up has been attributed to ester group reduction by the AlR3 cocatalyst. We have now measured the activation parameters for the reactions of ethyl benzoate (EB), dibutyl phthalate (DBP), and diethyl 2, 3‐diisobutylsuccinate (DiBS) with AlEt3 in toluene solution by means of variable‐temperature 1 H NMR spectroscopy. Reduction is fast for EB and DBP, whereas it is slow for DiBS. Results of DFT calculations are in line with the observed reactivity. Therefore, we conclude that an irreversible reaction with AlEt3 is not the only option for ID/ED exchange. Possible alternatives are discussed. Abstract : React or just bind? The activation parameters for the reaction of AlEt3 with three esters used as internal donors in industrial Ziegler–Natta catalysts for polypropylene synthesis, namely, ethyl benzoate, dibutyl phthalate, and diethyl 2, 3‐diisobutylsuccinate, were measured and correlated with the possible mechanisms for the cleaning‐up action of the catalytic surfaces by AlEt3 in view of stereoselectivity modulation with an external donor.